Improvement of Bamboo Crafts in Family Economy Post Covid-19 Pandemic: - Siska Dwi Yulianti; Roni Fardiansyah; Barkah Yasarudin (Institute of Computer Science (IOCS), 2022)
This research is motivated by the declining income of Bamboo Craft craftsmen in Cibiru Village (Egrang Village) Cicantayan Village, Kec. Cicantayan Kab. Sukabumi, West Java, during a pandemic that had an impact on the economic condition of Muslim families. In this case, the researcher wants to see how the economic condition of Muslim families as bamboo craftsmen after the Covid-19 pandemic will continue to decline or improve for the better. Through Bamboo Crafts, the people of Egrang Cibiru Village, Cicantayan Village, earn income that can be used to meet their daily needs while conserving and maintaining the Bamboo ecosystem around their homes. This study uses a qualitative phenomenological research method, which emphasizes how the living conditions of people who experience the use of bamboo in their daily lives. The results of this study were Bamboo Craft craftsmen before the Covid-19 Pandemic, they were able to reap profits of approximately between 50 - 80 thousand per day. During the pandemic, they sometimes only get 20 - 30 thousand and even then it is uncertain, so their income during the pandemic is very low which ultimately disrupts the economy. When the pandemic condition is almost over, it means that it can be said that currently post-covid-19 pandemic has increased by around 80%, even though this income is not the same as before the pandemic, bamboo craftsmen are very happy because they can maintain their family's economy and continue to be involved in preservation of national culture through bamboo.